2014
DOI: 10.1097/qai.0000000000000234
|View full text |Cite
|
Sign up to set email alerts
|

Role of Community-Level Factors Across the Treatment Cascade

Abstract: Addressing community-level factors (CLFs) is integral to the ongoing effort to design multilevel, effective, and sustainable interventions to address each element of the HIV/AIDS treatment cascade. This review, the first critical review of this topic, identified 100 articles that (1) assessed CLFs in relation to the HIV/AIDS treatment cascade, (2) had been peer-reviewed, and (3) were based on studies conducted in low- or middle-income countries. Social support and social networks, cultural norms, gender norms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 94 publications
1
48
0
2
Order By: Relevance
“…3,11 As monitoring of HIV infection increasingly focuses on the HIV care continuum 1114 , analyses of public health surveillance data may reveal geographic patterns that vary at each step. 15,16 Moreover, a better understanding of the structural and community-level factors that influence or impede completion of HIV care continuum steps is needed 1723 .…”
Section: Introductionmentioning
confidence: 99%
“…3,11 As monitoring of HIV infection increasingly focuses on the HIV care continuum 1114 , analyses of public health surveillance data may reveal geographic patterns that vary at each step. 15,16 Moreover, a better understanding of the structural and community-level factors that influence or impede completion of HIV care continuum steps is needed 1723 .…”
Section: Introductionmentioning
confidence: 99%
“…Discourses of the care cascade imply certain kinds of patient expectation and responsibility. An extensive body of extant literature accentuates how social and environmental factors shape HIV treatment provision and engagement (Gari et al, 2013;Merten et al, 2010;Underwood, Hendrickson, Van Lith, Kunda, and Mallalieu, 2014). Additionally, critical perspectives in the social sciences have reflected upon HIV and its care as constituted through situated health practices, identities and subjectivities, with implications for different social and political contexts Whyte, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Socio-cultural factors have also been shown to be important determinants of MNCH behaviours in SSA, including ANC attendance (Ahmed et al 2010;Hiarlaithe et al 2014;Pell et al 2013;Simkhada et al 2008;Underwood et al 2014). A study on facility delivery in northern Ghana, for example, found that traditional power hierarchies in the household and communities influenced the uptake of key health-seeking behaviours, and that often "someone must give the order", potentially hindering uptake of essential MNCH behaviours (Moyer et al 2014).…”
Section: Challenges For Antenatal Care In Sub-saharan Africamentioning
confidence: 99%
“…Ghana instituted its National Health Insurance Scheme (NHIS) in 2003 -with a primary objective to limit cost as a barrier to accessing MNCH services. A recent study in northern Ghana illustrated that enrolment in the NHIS had a positive association with uptake of institutional delivery; however, there was no effect on women's attendance of four or more ANC visits (Singh et al 2015).Socio-cultural factors have also been shown to be important determinants of MNCH behaviours in SSA, including ANC attendance (Ahmed et al 2010;Hiarlaithe et al 2014;Pell et al 2013;Simkhada et al 2008;Underwood et al 2014). A study on facility delivery in northern Ghana, for example, found that traditional power hierarchies in the household and communities influenced the uptake of key health-seeking behaviours, and that often "someone must give the order", potentially hindering uptake of essential MNCH behaviours (Moyer et al 2014).…”
mentioning
confidence: 99%